Exploring language production, comprehension and naming in adolescents with fetal alcohol spectrum disorders - Corbett, Claire (Department of Psychology, 2014)
The aims of this study were i) to evaluate the domains of language production, comprehension and naming in children with moderate or heavy prenatal exposure to alcohol, and ii) to determine if these domains are a specific weakness in these children. The study compared 25 children with FASD to 25 typically developing non-alcohol exposed controls on four language measures; (1) the Clinical Evaluation of Language Fundamentals Revised; (2) the Test of Reception of Grammar- Version II; (3) the Cookie Jar Theft Picture test and; (4) the Boston Naming test.